PELAKSANAAN PEMUNGUTAN PAJAK RESTORAN DALAM MEMAJUKAN SUMBER PENDAPATAN DAERAH DI KECAMATAN MARPOYAN DAMAI PEKANBARU BERDASARKAN PERATURAN DAERAH NOMOR 06 TAHUN 2011 - Linus Chyndy Efram Sianipar; Mexsasai Indra; Abdul Ghafur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Taxes as a source of state income, should provide as much financial income to the State. For the purposes of the tax regulated under the Act to force the taxpayer to fulfill its obligations to the State. With the rapidly growing business sector restaurants and eating houses local government issued regulations on taxes restaurants and eating houses No. 6 of 2011. Based on this understanding, the writing of this thesis formulated three formulation of the problem, namely: First, how How Implementation of Tax Collection Restaurants In Advancing Source Regional income In Sub Marpoyan Peace Pekanbaru Based on Regional Regulation No. 06 of 2011? Second, if the What constraints in the implementation of Tax Collection Restaurant And In Advancing Source Regional Revenue In Sub Marpoyan Peace Pekanbaru Based on Regional Regulation No. 06 of 2011? Third, if the attempt Any attempt to overcome obstacles Tax Collection Restaurant And In Advancing Source Regional Revenue In Sub Marpoyan peace Pekanbaru Based on Regional Regulation No. 06 of 2011?From the research there are three main issues that can be inferred, first, Implementation of Tax Collection Restaurants In Advancing Regional Revenue Sources Pekanbaru in District Marpoyan Peace Based on Regional Regulation No. 06 of 2011 has not been performing well. This is evident from the law enforcement aspect of the weak against the taxpayer restaurants that do not comply or violate the provisions of the regulation of local taxes until the deadline specified in the payment of taxes restaurants. Second, obstacles faced include lack of awareness of taxpayers in paying taxes and not maximal restaurant for collection of local taxes, especially in the case of unavailability of data on potential taxes. Third, efforts to overcome obstacles Restaurant Tax Collection Revenue Sources In Promoting Regional Peace In District Marpoyan Pekanbaru Based on Regional Regulation No. 06 of 2011, among other socialization and coaching Tax Collection Officer.Keywords: Implementation - Harvesting - Restaurant Tax